Bio‐Inert Surfaces: Design of Blood‐Compatible Interfaces with Poly(vinyl ether)s (Adv. Mater. Interfaces 12/2016). Issue 12 (June 2016) - Oda, Yukari; Zhang, Cui; Kawaguchi, Daisuke; Matsuno, Hisao; Kanaoka, Shokyoku; Aoshima, Sadahito; Tanaka, Keiji
Abstract : Diblock copoly(vinyl ether)s with oxyethylene side‐chains are designed to construct bio‐inert interfaces. The outermost region of the film in water is well characterized by sum‐frequency generation vibrational spectroscopy in conjunction with atomic force microscopy. Keiji Tanaka, Yukari Oda and co‐workers successfully demonstrate that the chemistry of the polymer side‐chain strongly impacts their interfacial properties in water, which contributes to the excellent blood‐compatibility in article 1600034.